Design, building and testing of a fibre optic force sensor and its application in an in vitro and in vivo study investigating the biomechanical properties of the patella tendon - Muller, Jacobus Hendrik (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScIng) -- University of Stellenbosch, 2007.